Abreviasi dalam Pesan Grup WhatsApp Siswa Sekolah Dasar - Nur Azizah; Arju Susanto; Tadjuddin Nur (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study delves into the utilization of diverse types of abbreviations in the context of WhatsApp group messages among sixth-grade students at SDN Karang Tengah 06. The research specifically focuses on identifying and categorizing abbreviations, acronyms, contractions, and fragments that are commonly employed. Employing qualitative research methods, including adept free-viewing and note-taking techniques, the investigation analyzes transcripts of group conversations involving class VI students in September 2022. The results of this analysis shed light on the prevalence of abbreviation usage within written communication among this cohort of 12 to 13-year-olds. Notably, the findings underscore the practicality of abbreviations in efficiently conveying information, especially considering the constraints of the medium. The data further reveals the intricate nature of these abbreviations, with many words exhibiting multiple forms of abbreviation. Through this research, a comprehensive understanding of the role and impact of abbreviation in contemporary written communication, particularly within the dynamics of adolescent peer groups, emerges, contributing to broader insights in the field.